Formulation of thymoquinone-loaded plga nanoparticles and cytotoxicity in malignant melanoma A375 cell line - Luqman Muizzuddin Mohd Rosli (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2020)
Background: Thymoquinone (TQ) has been known to have various therapeutic benefits but it is prone to fast degradation. TQ exhibited anticancer effect in several cancer cell lines. Encapsulation of TQ enhances its stability and provides a tool for targeting to the cancer tissues. Objective: To prepare and optimize TQ- poly-lactide-co-glycolide (PLGA) nanoparticle (NP) formulation and evaluate it in A375 cells for cell uptake and cytotoxicity. Methodology: TQ- PLGA NP formulation was prepared using solvent evaporation method and TQ quantification method was validated using HPLC. The total of 6 factors affecting the formulation (chitosan concentration (A), ratio of co-stabilizer (tween 80: polyvinyl alcohol (B), stabilizer concentration (C), ratio of co-solvents (ethyl acetate: dichloromethane) (D), sonication power (E) and sonication time (F), were screened using fractional factorial design. The screened factors were reduced to 3 most significant (A, C and E) affecting critical output responses of particle size, zeta potential and encapsulation efficiency. An optimized TQ-PLGA NP was prepared by altering these significant factors using full factorial design and targeted responses was acquired and it was proceed for cell uptake studies by flow cytometer and fluorescence microscope; and cell cytotoxicity studies by MTT assay. Results and discussion: Optimized TQ-PLGA NP formulation was prepared using 1.02 % w/v chitosan, 1.14% w/v stabilizer and 31% of sonication power. The rest of the parameters were fixed as 1:3 oil to aqueous phase ratio, 1:5 primary emulsion to dispersion medium ratio, 3% w/v PLGA concentration and 75:25 co-solvent ratios of ethyl acetate and dichloromethane. TQ-PLGA NP exhibited particle size of 147.2 ± 0.4 nm; polydispersity index (PDI) of 0.142 ± 0.017; zeta potential of 22.1 ± 1.1; encapsulation efficiency of 96.81 ± 0.05 %; biphasic release of 56.7 ± 1.3% (24 h) and 69.7 ± 1.3% within 1 week. The optimized formulation was aggregated in powdered form but stable in the suspension form up for 10 days. The formulation exhibited lower glass transition of PLGA below 37°C suggesting a plasticizing effect of TQ and other ingredients which contributes to the overall rapid release. TQ in methanol and TQ-PLGA NP in complete growth media were tested for stability. TQ degraded by 18% (24 h) and 77.0% (48 h), particle size remains stable in 24 h, significant changes occurred after 48 h (p < 0.05), PDI changes were significant post 24 h and 48 h (p < 0.05), significant changes on zeta potential were observed on higher concentration of TQ-PLGA NPs (p < 0.05). The highest intracellular uptake was at 1.0 mg/mL NP concentration with time-dependent cell uptake up to 24 h. Post 24 h treatment, the IC50 of TQ-PLGA NP and TQ-solution was calculated to be 4.428 mg/mL and 91.71 µg/mL respectively. At 48 h treatment, IC50s of TQ-PLGA NP was calculated to be 7.981 mg/mL and 58.657 mg/mL respectively. Conclusion: Optimized TQ-PLGA NP was formulated and it showed a promising cytotoxic effect in A375 cells. TQ in nanoparticle formulation has a potential use as anticancer and worth a further study in animal models.